2018
DOI: 10.1111/iej.12900
|View full text |Cite
|
Sign up to set email alerts
|

Systemic bone marker expression induced by grey and white mineral trioxide aggregate in normal and diabetic conditions

Abstract: Both MTA materials were associated with an increase in serum calcium, phosphorus and ALP, suggesting a potential systemic effect, along with triggered differentiation of OCN- and OPN-positive cells. Moreover, in diabetic conditions, an inhibitory effect on MTA-induced differentiation of OCN- and OPN-positive cells was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
(134 reference statements)
1
9
0
Order By: Relevance
“…In addiction, cytokines production and inflammatory response were not upregulated in hyperglycemic animals; however, a decrease in the calcium deposition was observed in presence of WMTA, suggesting a delay in the mineralization process [165]. These results are supported by a previous study that found in diabetic conditions an inhibitory effect on MTAinduced differentiation of OCN-and OPN-positive cells was detected [173].…”
Section: Impact Of Systemic Disorders On Biomineralization Of Endodon...supporting
confidence: 82%
“…In addiction, cytokines production and inflammatory response were not upregulated in hyperglycemic animals; however, a decrease in the calcium deposition was observed in presence of WMTA, suggesting a delay in the mineralization process [165]. These results are supported by a previous study that found in diabetic conditions an inhibitory effect on MTAinduced differentiation of OCN-and OPN-positive cells was detected [173].…”
Section: Impact Of Systemic Disorders On Biomineralization Of Endodon...supporting
confidence: 82%
“…Sixteen 2-month-old male Wistar rats weighing from 250 to 280 g were used. The sample size was established based on previous studies involving the analysis of materials in the subcutaneous tissue of rats (Cintra et al 2013, de Azevedo Queiroz et al 2018, Benetti et al 2018a. The animals were housed in a temperature-controlled environment (22 AE 1°C, 70% humidity) with a 12-h light-dark cycle and received water and food ad libitum.…”
Section: Biocompatibility and Biomineralization Analysismentioning
confidence: 99%
“…Finally, it has been reported that systemic disease can influence the efficiency of MTA in endodontics. For instance, diabetes mellitus could inhibit mineral differentiation in subcutaneous implantation (de Azevedo et al, 2018) and dentin bridge formation in rat pulp capping (Garber et al, 2009). So when calcium silicate-based bioceramics are applied in patients with systemic disease, the control and treatment of the systemic disease should be carried out ahead of any procedures to improve the success rate of calcium silicatebased bioceramics in endodontics.…”
Section: Conclusion and Perspectivementioning
confidence: 99%